Thidiazuron como promotor de brotos múltiplos em explantes de algodão (Gossypium hirsutum L.) (Acta Scientiarum. Agronomy, 2008)
Most cotton Gossypium hursutum (Malvaceae) genotypes of commercial interest present problems of in vitro regeneration. Aiming at improving regeneration rate, meristems and caulinar apices (region with about 5 mm length, immediately below the meristematic region) of IAC 22 and COKER 312 cultivars were extracted from plants with 2 or 3 primordia leaves and grown in Murashige and Skoog (MS) medium containing thidiazuron (TDZ), with concentrations ranging between 0.02 µM and 5.0 µM, in 3- to 7-day periods, with naphthaleneacetic acid (NAA) and gibberellic acid (GA3). The number of shoots from meristems was higher in 0.02 µM TDZ concentrations. In the case of caulinar apices, best results were obtained with 0.5 and 1.0 µM of TDZ. Abundant callus formation, length reduction of plant and inhibition of root formation were caused by the addition of TDZ. Propagation rate was comparable to other results for cotton reported in the literature